A Corpus-Informed Grammatical Profile of Indonesian Pop Lyrics: Word-Class Distribution and Denotation in Mahalini’s Fabula - Nabila Nurrahma; Ali Akbar Jono; Vebi Andra (Yayasan Darussalam Bengkulu, 2024)
Despite the widespread pedagogical use of songs, corpus‑informed grammatical profiles of Indonesian pop lyrics remain scarce. This study therefore maps the distribution of Indonesian word classes and inventories denotative meanings in the official lyrics of the ten tracks on Mahalini’s Fabula. Using a qualitative content‑analysis design, we tokenized the corpus by orthographic word and annotated each token into one of ten classes (verba, adjektiva, nomina, pronomina, numeralia, adverbia, interogativa, demonstrativa, preposisi, konjungsi); denotative senses were then assigned with reference to KBBI VI Daring and resolved by local context. Descriptive statistics summarize the resulting profile of 323 lexical tokens and 157 denotative senses. Verbs dominate the lexicon (26.93%), followed by adjectives (15.79%) and pronouns (15.17%), with conjunctions (10.22%) and adverbs (8.98%) forming a mid‑frequency band and nouns (6.19%), interrogatives (5.26%), demonstratives (4.64%), prepositions (4.02%), and numerals (2.79%) comparatively infrequent. The pattern indicates an affect‑centred narrative style driven by processes, evaluative lexis, and deictic anchoring. The study contributes a replicable annotation protocol and a compact, clean dataset that can inform stylistic comparisons and instructional design. While limited to a single album and without inter‑rater reliability or figurative/pragmatic layers, the findings provide a baseline for broader lyric corpora. Results guide Indonesian‑language pedagogy toward high‑yield resources (process verbs, evaluative adjectives, pronominal systems), support corpus‑based stylistics across artists and subgenres, and offer benchmark material for Indonesian NLP in creative registers.